Role of nitric oxide in the immunosuppressive effect of trypanosoma lewisi on multiplication of toxoplasma gondii in white rats - Ríos Carrera, Nivia Judith (2013)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 2013